Multicultural variations : social incorporation in Europe and North America - Roberts, Lance W., 1950-2019; Ferguson, Barry, 1952-; Bös, Mathias; Below, Susanne von, 1965- (Comparative charting of social change., 2013)
How symbolic rather than institutionalized multiculturalism characterizes ethnic social incorporation for new groups experiencing the recognition of ethnic pluralism.